Definite generic vs. definite unique in L2 acquisition. (31st August 2018) - Snape, Neal
This study examines the role of universal meanings in second language (L2) acquisition by specifically looking at whether Japanese L2 learners of English can distinguish between definite generic the and definite unique the . Japanese is a language that has no definite (or indefinite) article, but the meanings expressed with definite generic and definite unique in the L2 should be accessible to L2 learners if they have full access to universal meanings. The difficulty for L2 learners is mapping features from the L1 to new L2 morphology (Lardiere, 2016 ). We employed a picture matching task (PMT) and a forced-choice elicitation task (FCET). For the PMT, participants had to match a sentence with one or more than one picture in each set of four pictures. Definite generic can refer to more than one individual when it is accompanied by a predicate like be extinct : one picture of a single dodo bird AND a picture of a set of dodo birds can refer to the entire species of dodo bird. Definite unique is when the definite article refers to one individual. The FCET required participants to select an article to fill-in-a-blank with an article they felt most appropriate. We recruited 47 Japanese L2 learners of English in total and 26 native speakers of English. The results show that L2 learners perform as well as the native speaker controls on the PMT for definite generic and definite unique, but the FCET results reveal differences between the two groups for definite generic and definite unique.